Fall Risk Assessment Methods Among Older Adults: A Literatur Review - Dwi Elma Miftahul Jannah; Nursalam Nursalam; Kristiawati Kristiawati (GLOBAL HEALTH SCIENCE GROUP, 2025)
The elderly often experience a decline in balance, functional ability, and mobility, increasing their susceptibility to falls and serious injuries. This study aimed to identify commonly used methods for assessing fall risks in the elderly through a literature review. Methods: The review focused on individuals aged >60 years and included studies assessing fall risk factors such as physical weakness and motor reaction time improvement. Cross-sectional studies and full-text journal articles were selected from four databases (ScienceDirect, ProQuest, PubMed, and SAGE Research Methods) covering the period from January 2019 to December 2024. The inclusion criteria involved studies focusing on fall risk factors, while exclusions included COVID-19-related studies, abstracts, reviews, discussion papers, letters to editors, and articles without full texts. Results: A total of 10 journal articles involving 15,274 elderly respondents were reviewed. Demographic data included age, gender, marital status, economic status, environment, weakness, medical history, and fall history. Various assessment methods were identified, with the most frequently used being fall questionnaires (26%), MMSE (17.3%), balance and fall scales (13%), physical activity assessments (8.6%), motor reaction time tests (8.6%), and BMI evaluations (8.6%). The data showed that methods with higher usage percentages are commonly employed to determine fall risks in the elderly. Conclusions: Fall risk assessments utilize diverse methodologies, including physical tests, mental health evaluations, and interviews. Notably, fall risk measurement methods have proven effective in preventing falls in this population.